The Impact of Anti-Violence Law on Changes in Santri Organization at Modern Islamic Boarding Schools (Pesantren) - Zainal, Suadi (Institut Agama Islam Negeri Lhokseumawe, 2022)
Dayah Ulumuddin is an Islamic residential school that operates on a 24-hour basis. The santri organizational system requires senior santri to enforce norms and discipline. Junior students may be subjected to corporal punishment as a result of this dynamic. The passage of the Child Protection Act ensures that students are safe from assault and discrimination. This situation necessitates the renewal of pesantren education administration, particularly that of santri groups. This study intends to: (1) characterize changes in student organization as a result of the anti-violence law; and (2) describe and identify the impacts that occur as a result of the anti-violence law's passage. The study was conducted in a qualitative manner. Data gathering techniques like as interviews, participant observations, and documentation are used to collect data in an open form (funnel). Techniques for data analysis include data condensation, data display, and drawing conclusions/verification. The study's findings indicate that the passage of the anti-violence law has an institutional impact on changing the work system of the Santri organization, as well as an individual emergence of apathy among senior educators and pupils for fear of being caught up in the law. Another unfavorable effect is an increase in the graph of disciplinary offenses.